Tourism and Political Change. - Butler, Richard (Goodfellow Publishers Ltd, 2017)
Tourism is a vital tool for political and economic change. With international contributions from experienced individuals, this book cover general themes and issues, with three thematic sections with original chapters, and a concluding section. It covers a variety of international political changes at different scales and their resulting effects.